Sistem Informasi Akuntansi (SIA) sebagai Katalisator Good Governance dan Akuntabilitas Sektor Publik: Tinjauan Sistematis Literatur dan Agenda Penelitian Masa Depan - Feranika Meilinda; Novi Dinda Arifia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
In order to thoroughly examine and compile the body of research on the function of the Accounting Information System (AIS) as a catalyst for Good Governance (GG) and Accountability in the public sector, this study does a Systematic Literature Review (SLR). The major goals are to ascertain the key obstacles and opportunities in attaining real-time accountability in Indonesia (RQ2) and to identify the most important AIS aspects (input, process, and output) driving public sector accountability (RQ1). AIS quality, apparatus competency, and the efficacy of internal control systems are the most important factors that consistently affect the quality and timeliness of public financial statements, acting as the fundamental mechanism for accountability, according to the synthesis, which uses a strict screening protocol across multiple academic databases. The evaluation does, however, draw attention to widespread implementation issues, which are mostly caused by weak organizational commitment, user resistance, and inconsistent ethical standards among public officials. In order to close the gap between theoretical potential and real-world application for sustainable good governance, these findings not only resolve the contradictions in earlier research but also produce a Future Research Agenda that suggests a move toward Action Research and the study of cutting-edge technologies (like Blockchain or Big Data Analytics) in AIS.